How States Become Fragile: Relevancy of State Fragility and Climate Change - Zhang, Sirui; Chen, Jiebin; Wu, Hao-Ning; Ye, Shiqi (E3S web of conferences, 2018)
The objective of this article is to develop a main index that is capable of determining a state, s fragility and simultaneously measuring the impact of climate change. Six indexes are defined including a dummy one, which are Political Conditions, Economic Conditions, Social Conditions, Demographic Factor, Public Security and State Unrest (dummy). Five non-dummy indexes are involved four sub-indexes respectively. The sum of these six indexes is reported as State Stability Index (SSI). Entropy method and group decision making serve as weighting models to determine weights of sub-indexes and indexes respectively. A state, s fragility is determined by State Fragility Index (SFI), which is the reciprocal of SSI. Five non-dummy indexes and SFI have their standards obtained by K-means, in order to determine whether a state is fragile, vulnerable or stable.